Simian virus to (SV40) tumor-specific proteins in nucleus and plasma membrane of HeLa cells infected by adenovirus 2-SV40 hybrid virus Ad2+ND2. - Deppert, W (1976)
HeLa cells infected with the nondefective adenovirus 2-SV40 hybrid virus (Ad2+ND2) have previously been shown to synthesize two SV40-specific proteins with molecular weights of 56,000 (56 K protein) and 42,000 (42 K protein). The present study demonstrates that these proteins are immunoprecipitable with serum from hamsters bearing SV40 tumors. By peptide analysis, it is shown that the 56 K and 42 K proteins share common amino acid sequences. Both proteins are metabolically stable in nuclei and plasma membranes but unstable in the cytoplasm, as shown by pulse-chase experiments and cell fractionation studies.